Synthesis and development of novel sensitizer from Spirulina pigment with silver doped ZnO nano particles for bio-sensitized solar cells - S. Ranjitha; S. Bhuvaneswari; C. Sudhakar; V. Aroulmoji (Chemical Physics Impact)
Phycocyanin from Spirulina (blue-green algae) is used as photosensitizer to fabricate biosensitized solar cells (BSSC). Pigments are extracted in different solvents such as water, ethanol and acetone. Pure and silver-doped ZnO nanoparticles were prepared by simple microwave technology, and BSSCs were prepared by spin coating method. The structure, morphology, optical properties and electrochemistry of the prepared materials were examined by powder X-ray diffraction, field emission scanning electron microscopy (FE-SEM), transmission electron microscopy (TEM), ultraviolet-visible light spectroscopy and electrochemical impedance spectroscopy. The main observation of this research is the decrease of the energy band gap value due to doping of “Ag” ions, which will delay the recombination rate and increase the photovoltaic conversion efficiency by 2.87 % compared to pure ZnO nanoparticles (0.74 %). The photocurrent density-photo voltage (J-V) characteristics of fabricated BSSC using Pycocyanine pigments under various solvent-adsorbed conditions on nanocrystalline pure ZnO and Ag-doped ZnO film electrodes were carried out. The pigments in association with the water solution show the short-circuit photocurrent density Jsc of around 9.80 mA/cm2 and the open-circuit photovoltage Voc of 0.84 V, under an illumination intensity of 40 mW/cm2 respectively. The results of the present study reveals that “Ag” doped ZnO nanoparticles may be a promising candidate for the future BSSC applications.